If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -6 = 8(x + -9) Reorder the terms: -6 + 3x = 8(x + -9) Reorder the terms: -6 + 3x = 8(-9 + x) -6 + 3x = (-9 * 8 + x * 8) -6 + 3x = (-72 + 8x) Solving -6 + 3x = -72 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -6 + 3x + -8x = -72 + 8x + -8x Combine like terms: 3x + -8x = -5x -6 + -5x = -72 + 8x + -8x Combine like terms: 8x + -8x = 0 -6 + -5x = -72 + 0 -6 + -5x = -72 Add '6' to each side of the equation. -6 + 6 + -5x = -72 + 6 Combine like terms: -6 + 6 = 0 0 + -5x = -72 + 6 -5x = -72 + 6 Combine like terms: -72 + 6 = -66 -5x = -66 Divide each side by '-5'. x = 13.2 Simplifying x = 13.2
| -10+3x=-2x+45 | | 8x-2=9+7y | | .20x+x=60 | | 3(x-1)-2=1/2(4x-8) | | (x+11)+(x+19)=16 | | y^2-36y-64=0 | | .6x+6.6=3.3 | | y^2-36y+64=0 | | m^3-121m=0 | | y=-0.80(25)+136 | | 14+2k-22=k | | -5y+4y+16=-56 | | 6+2(1x+-5)=2x+-4 | | .28x+3=0.14 | | 20y-5=3(y-47) | | -6x+9=20-4x | | -3x+3=x-25 | | 2[3-3(x+1)]+1=2(-15-x)+2x+15 | | 20-2=205 | | v-7+8=19 | | 3x-50+2x-5=180 | | 9a^3b^2+12ab^2=0 | | 85+4=99 | | 30*x/30= | | -0.6(5x)=90 | | 1.8+n=15.72 | | 7x-5=4x-41 | | 2x+3x-8=22 | | 3*x/30= | | 25-8=12.5 | | 3.6x=5.4+3.3x | | 9+2.7x=-4.8x-6 |